Media Relations Activity of Daerah Istimewa Yogyakarta Regional Government Public Relations in Fostering Good Relations with The Mass Media 2024 - Tsaniah, Raden; Ishak, Aswad (Jogjakarta Communication Conference (JCC), 2025)
The Special Region of Yogyakarta (DIY) Regional Government is the example of a unique case in handling media relations. Different structures of governance may have an impact on the media relations that are run by the Special Region of Yogyakarta Regional Government Public Relation. Nevertheless, seeing how open the government public relations team is in catering the media needs, the author is interested to learn more about how the Public Relations activities of the DIY Regional Government establish and maintain effective media relations to foster positive public perception and ensure the successful dissemination of information. This study examines the media relations activities of the Daerah Istimewa Yogyakarta (DIY) Regional Government's Public Relations division in fostering good relationships with the mass media in 2024. In the modern era, where transparency and information sharing are vital, establishing strong media relations is essential for the government to effectively communicate policies and initiatives to the public. The research aims to identify how the DIY Public Relations department navigates media relations, focusing on strategies that are used to maintain positive relationships with journalists and media outlets. This research was conducted by qualitative methods, including interviews with DIY regional government public relations staff and media representatives, the study explores how the regional government maintains good media relations practices while ensuring that the activities carried are aligned with public relations concepts. According to the findings, the DIY Public Relations department takes a proactive and open approach, not only a personal approach but also an institutional approach. They also make sure journalists have easy access to information by developing an Early Warning System (EWS). In conclusion, the Yogyakarta Special Region Provincial Government's Public Relations team utilizes both personal and institutional approaches to foster positive media relations. Their proactive strategies, including the development of an Early Warning System, ensure effective communication and transparency with the media, supporting a strong public perception.